Beyond the Secular West - Bilgrami, Akeel (Religion, Culture, and Public Life, 2016)
What is the character of secularism in countries that were not pervaded by Christianity, such as China, India, and the nations of the Middle East? A vital extension of Charles Taylor's A Secular Age, which chronicled the emergence of secularism in Latin Christendom, this anthology applies Taylor's findings to secularism's global migration. Contributors explore the transformation of Western secularism beyond Europe, and the collection closes with Taylor's response to each essay.